2021
DOI: 10.5435/jaaos-d-20-00880
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of the Walch Classification for Primary Glenohumeral Arthritis

Abstract: Our understanding of the pathology of and treatment for glenohumeral arthritis (GHA) has grown dramatically in the past few decades. Original observations regarding patterns of glenoid erosion, glenoid retroversion, and posterior humeral head subluxation in patients with primary GHA were documented in the 1980s and early 1990s. In the late 1990s, Walch et al proposed what is now the most widely used classification system to describe the characteristic pathology of GHA. Improved understanding of both premorbid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…All patients treated surgically with the DJO/Encore Reverse Shoulder Prosthesis (DJO, Austin, TX, USA) augmented with a humeral head autograft were identified. These cases were further stratified according to the Walch classification (A2, B1, B2, B3, C1, C2, and D), 8 , 13 the Favard classification (E0, E1, E2, E3, and E4), 8 , 15 and whether they had concomitant rotator cuff insufficiency. The Walch and Favard classifications have only been validated for cases of primary osteoarthritis and massive rotator cuff tear, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients treated surgically with the DJO/Encore Reverse Shoulder Prosthesis (DJO, Austin, TX, USA) augmented with a humeral head autograft were identified. These cases were further stratified according to the Walch classification (A2, B1, B2, B3, C1, C2, and D), 8 , 13 the Favard classification (E0, E1, E2, E3, and E4), 8 , 15 and whether they had concomitant rotator cuff insufficiency. The Walch and Favard classifications have only been validated for cases of primary osteoarthritis and massive rotator cuff tear, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Type B2, B3, C2, and D all involve moderate to severe bone loss with glenohumeral subluxation. 8 , 13 These morphologies can also be associated with bone loss to the glenoid vault depth, precluding implantation of a cemented standard glenoid component in anatomical shoulder arthroplasty, and reduced bone stock for implantation of reverse total shoulder ingrowth componentry. 8 , 18 It has been reported that up to 40% of patients with rotator cuff arthropathy present with superior bone loss to the glenoid.…”
mentioning
confidence: 99%
“…Radiological loosening of the glenoid component is one of the most common complications of TSA, especially in patients with associated rotator cuff deficiency. Although literature exploring the correlation of the Walch classification to clinical outcomes after anatomic TSA is limited, this high rate of radiologically loosening suggests that the use of cemented polyethylene components should be avoided, especially in young patients who do more lifting and pulling 79,83 . Despite complications, a study by Favard et al shows low revision rates in most TSAs, good long-term clinical function, and a relatively high rate of satisfaction 79 .…”
Section: Surgical Interventionmentioning
confidence: 99%
“…Walch et al [ 6 ] described three glenoid wear patterns that have subsequently been expanded upon: A or concentric wear, B or posterior/eccentric wear, and C or dysplastic glenoids. B glenoids can be further described as B1 or monoconcave, B2 or biconcave glenoids, and B3 or monoconcave glenoids with posterior subluxation >70% or retroversion > 15% [ 7 ]. Glenoid deformity can influence treatment decisions with neoglenoid retroversion of greater than 27 degrees leading to an increased risk of glenoid component loosening [ 8 ].…”
Section: Introductionmentioning
confidence: 99%